1986
DOI: 10.2466/pr0.1986.59.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment Disorders and Suicidality

Abstract: In this study two rating scales, the Echelle d'Evaluation de Risque Suicidaire and the Pierce-modified form of the Suicide Intent Scale, were administered to a group of 43 persons admitted to the general hospital of Padua for suicide attempts. The purpose of our study was to verify whether these tools could be considered useful in the assessment of severity of the attempts. The rating scales showed good concordance in identifying the adjustment disorder group as less dangerous for the seriousness of the attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…These findings are in agreement with those of De Leo et al (15), who reported that suicidal risk is higher in major depressed than in minor depressed patients. In other words, suicidal ideation increased along the depressive spectrum of depressive subtypes, i.e.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings are in agreement with those of De Leo et al (15), who reported that suicidal risk is higher in major depressed than in minor depressed patients. In other words, suicidal ideation increased along the depressive spectrum of depressive subtypes, i.e.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in agreement with those of De Leo et al (15), who reported that suicidal risk is higher in major depressed than in minor depressed patients. De Leo et al (15) postulated that psychological stressors which lead to an adjustment disorder, such as divorce, serious family problems, a professional crisis, etc., mean that some subjects attempt suicide more readily in order to influence their environment. In the present study, we were unable to demonstrate a significant relationship between the depression subgroups and the number of depressed patients who had attempted suicide.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although future research may ultimately show that adjustment disorder is a form of subclinical depression, the fact remains that persons identified as having adjustment disorder are often associated with being at risk for increased morbidity and even mortality (i.e., suicide). 63 It is important to note that persons with adjustment disorder have been shown to have positive outcomes when treated with brief psychotherapy. 64 This allows for the possibility of early intervention before a problem worsens to the point of requiring more intensive care and medications.…”
Section: Adjustment Disordermentioning
confidence: 99%